STUDI KASUS STABILITAS STRUKTUR TANAH LEMPUNG PADA JALAN TOTOK KEROT KEDIRI MENGGUNAKAN LIMBAH KERTAS - Agata Iwan Candra; Sulik Anam; Zendy Bima Mahardana; Andri Dwi Cahyono (U Karst, 2018)
The stability of the soil structure is something that needs to be considered in development. Increasing soil structure improvement can be done through various efforts using added materials or compaction processes. This study aims to improve the clay soil on the kerot kediri road using paper waste. The research was conducted experimentally by making samples in the laboratory. The land used is from the Totok Kerot road, Kediri, which has damaged the road surface due to land loans. Waste paper was added at 0% 7.5%, 10%, 15%, and 20% of the weight of the test object. Waste paper is used with pulp after it is dried and pulverized to a certain gradation. The tests carried out include the Consistency Limit (Atterberg Limit) and Soil Compaction (Proctor) tests. The results showed that the addition of waste paper affects the original properties of the soil. The addition of paper moisture content decreases the Plastic Index value and increases the dry volume of the soil. The addition of waste paper content also increases the volume of dry soil water but decreases after reaching the optimum point, namely at 10% paper waste content and 9.96% water content with a dry volume weight value of 1.97gr/cm3. The greater the dry volume of soil, the dry density indicates that the soil is getting higher. So that by knowing these results, it can be used as a reference in the process of repairing and backfilling the soil on the Totok Kerot Kediri road.